Effect of calcium and vitamin D supplementation on serum calcium level in children with idiopathic nephrotic syndrome - Vaya Dasitania; Alex Chairulfatah; Dedi Rachmadi (Indonesian Pediatric Society Publishing House, 2014)
Background Patients with idiopathic nephrotic syndrome (NS) may develop hypocalcemia caused by low levels of albumin and vitamin D -binding protein, which subsequently decreases calcium absorption in the intestine. Hypocalcemia may result in neuromuscular manifestations, such as Chvostek's and Trosseau's signs. Objectives To evaluate the effect of calcium and vitamin D supplementation on hypocalcemia and its clinical manifestations in idiopathic NS children. Methods A randomized, single-blind, controlled trial was performed in idiopathic NS patients aged 1-14 years. Subjects were divided into treatment and placebo groups. Subjects in the treatment group received 800 mg elemental calcium and 400 IU vitamin D supplementation, while they in control group received placebo syrup, both for 8 weeks. Serum calcium and manifestations of hypocalcemia were examined before and after supplementation. Results Thirty subjects completed the study (15 in each group). Seventeen subjects experienced hypocalcemia. Chvostek's and Trosseau's signs were observed in 6 subjects in the treatment group and 2 subjects in the placebo group (P= 0.427). After 8 weeks of intervention, Chvostek's and Trosseau's signs disappeared in both groups, and calcium levels were significantly increased in both groups compared to the levels before intervention. However, there was no significant difference in serum calcium levels after 8 weeks between the treatment and placebo groups (P =0.707). Conclusion Normalization of serum calcium levels and improved clinical manifestations ofhypocalcemia occur both in NS patients who receive calcium and vitamin D supplementation and those who do not.